2015
DOI: 10.1177/0268355515580473
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of electrostimulation in augmentation of venous blood flow after total knee replacement: A pilot study

Abstract: Electrostimulation of the common peroneal nerve enhanced venous flow in the lower limb and may potentially be of use as a supplementary technique in deep venous prophylaxis following lower limb orthopedic operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The Geko ™ device is a battery-powered and disposable tool that is intended to reduce the risk of VTE [ 21 ]. It has been suggested that performing NMES in addition to pharmacological prophylaxis may be beneficial in reducing the incidence of DVT in patients undergoing orthopedic surgery [ 18 , 22 ]. In a systematic review evaluating the role of NMES in thromboprophylaxis, Hajibandeh et al concluded that NMES increased venous blood flow and was well tolerated, although current evidence does not promote the role of NMES in thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Geko ™ device is a battery-powered and disposable tool that is intended to reduce the risk of VTE [ 21 ]. It has been suggested that performing NMES in addition to pharmacological prophylaxis may be beneficial in reducing the incidence of DVT in patients undergoing orthopedic surgery [ 18 , 22 ]. In a systematic review evaluating the role of NMES in thromboprophylaxis, Hajibandeh et al concluded that NMES increased venous blood flow and was well tolerated, although current evidence does not promote the role of NMES in thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study of patients who underwent total knee replacement, Yilmaz et al found that postoperative femoral vein peak flow velocity was significantly higher among patients who received NMES (n=15, m=17.46, s=2.86)compared with those who did not receive it (n=15, m=13.84, s=3.58 cm/s, p=0.02) [ 22 ]. The mean femoral vein peak flow velocity increased by 67.48% with the postoperative NMES application compared with the preoperative values.…”
Section: Discussionmentioning
confidence: 99%
“…Electrostimulation group achieved a significant increase in peak blood flow velocity in the femoral vein after the operation (mean increase 67.48 AE 17.38%, p < 0.001). 9 Although there have been several studies investigating the effect of electrostimulation of venous blood flow, 10,11 data are limited on arterial blood flow. Tucker et al 6 conducted an experimental study on healthy volunteers and they found that electrostimulation caused a substantial increase of the microcirculatory flow in all stimulation settings.…”
Section: Discussionmentioning
confidence: 99%
“…Electrostimulation group achieved a significant increase in peak blood flow velocity in the femoral vein after the operation (mean increase 67.48 ± 17.38%, p < 0.001). 9…”
Section: Discussionmentioning
confidence: 99%